A new threat is on the horizon: The monkeypox virus. Should we worry about it or just keep an eye on it? - Gastón Sanglier Contreras (Open Journal of Pain Medicine - Peertechz Publications, 2022)
Monkeypox is a rare viral disease that is endemic in many African countries. However, within days, dozens of cases of monkeypox were confirmed in at least 12 non-African countries. It first appeared in the UK and was reported on 7 May 2022. The discovery of the virus in many patients and in different populations around the world within a few days raised the issue of scientific, medical, managerial, and social logic. The cases reported to date have no established travel links to endemic areas, but a recent mass event may have served as a focus for amplification. Epidemiological investigations are ongoing. With increased surveillance in non-endemic countries, it is likely that more cases of monkeypox will be identified and confirmed. With all this, we must ask ourselves, as we did with the advent of COVID-19, whether the population is seriously threatened and whether or not we should be concerned about the new virus in the future.